Comparison of Estradiol Cypionate, Estradiol Benzoate and Gonadotropin-Releasing Hormone in Fixed-Time Artificial Insemination in Multiparous Murrah Buffaloes - Nain, Satish; Kumar, Devender; Dholpuria, Sandeep; Choudhary, Ashok Kumar; Choudhary, Archana; Chahar, Satish Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was aimed to evaluate the efficiency of estradiol cypionate, estradiol benzoate and gonadotropin-releasing hormone during fixed-time artificial insemination (FTAI) protocols in multiparous Murrah buffaloes. A total of 35 buffaloes were used between September and November 2021 and subjected to a synchronization protocol. On day 0, insertion of an intravaginal progesterone device (CIDR, 1.38 g) was made with intramuscular (i/m) injection of estradiol benzoate (EB, 2 mg); On day 9: CIDR removed with i/m injections of Dinoprost (12.5 mg) and eCG (400 IU), and then buffaloes were randomized into three treatment group: 1) EB 1 mg on day 10 (n=13). 2) estradiol cypionate (EC) 1 mg on day 9 (n=12), and 3) Buserelin acetate (GnRH) 0.0105 mg on day 10 (n=10). The estrus signs observed during the FTAI (56 h after CIDR withdrawal) and conception rate at 90 days after FTAI were recorded. The conception rates were 61.5, 58.3 and 60.0% for EB, EC and GnRH treatment groups, respectively. There was no significant difference between the treatment groups for conception rate and signs of estrus. Therefore, it was concluded that all three treatments can be efficiently used during estrus synchronization protocol with FTAI in multiparous Murrah buffaloes.
Keywords: Buffalo farm; Conception; Estrus synchronization; Heat signs; Pregnancy